Tuning the magneto-electrical properties of multiferroic multilayers through interface strain and disorder - Sutter, J.G.; Chávez, A.S.; Soria, S.; Granada, M.; Neñer, L.; Bengió, S.; Granell, P.; Golmar, F.; Haberkorn, N.; Leyva, A.G.; Sirena, M.; Haberkorn, Néstor (Elsevier, 2021)
Fil: Gonzalez Sutter, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina